Explosive Power Analysis of Leg Muscles of Volleyball Players - Ardyansyah Arief Budi Utomo; Agung Dwi Darmawan; Ghon Lisdiantoro; Nopi Hariadi; Usman Wahyudi (Indonesian Journal of Kinanthropology (IJOK), 2026)
Background: Volleyball in Madiun City is increasingly competitive, so it is necessary to improve physical condition. The UNIPMA Volleyball Team won 2nd place in the PPMI Volleyball Cup in the framework of the 10th PPI Anniversary. Of course, this must be maintained and must always be improved. Therefore, an explosive analysis of the leg muscle power of male and female volleyball players at PGRI Madiun University in 2026 must be carried out as a basis for determining the training program. Method: This study uses a survey method using test and measurement techniques. This type of research is descriptive quantitative. The population is 30 athletes, a sample of 30 athletes as well, consisting of 15 male athletes and 15 female athletes. Using a total sampling technique. The test instrument uses a vertical jump test. Results: The results of male athletes with an average power of 439.2 joules / second (439 watts). The results of the female athletes' with an average power of 274.413 joules/second (274 watts). Conclusion: The power of male athletes with a percentage of 20% for the classification of "Very Good" and 80% for the classification of "Good". While the power of female athletes with a percentage of 40% for the classification of "Good" and 60% for the classification of "Medium".